Manajemen Pendidikan Islam Pada Masa Pemerintahan Sultan Sulaiman I Dinasti Turki Usmani (1520-1566) - Mardiah Mardiah; Riska Suci Febriani; Muslim Afandi (LPPM Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Sulaiman I was the greatest Sultan of the Ottoman Empire who made a major contribution to Islam. This research was conducted with the aim of knowing the management of Islamic Education during the reign of Sultan Sulaiman I in the Ottoman Empire. In this study, researchers used a type of library research (Library Research) with descriptive methods and historical approaches. Researchers used data collection techniques with documentation techniques, namely examining library sources such as journals, educational books, history books, and other relevant sources. The conclusion from this study is that during the reign of Sultan sulaiman Al- Qanuni in the Ottoman Turkish dynasty filled with developments and updates in various fields, including the field of education. In the context of Islamic education, the policies taken by Sultan Sulaiman Al-Qanuni played an important role in shaping and strengthening the Islamic education system of his time. At that time education was divided into three parts, namely family education, palace education, and madrasah. several important roles of Sultan Sulaiman Al-Qanuni, namely Building Educational Complexes, Improving Teacher Welfare, and Determining Teacher Career Paths